TEKNIK RELAKSASI PERNAPASAN DALAM: SOLUSI PENGURANGAN NYERI PERSALINAN KALA I FASE AKTIF - Gladeva Yugi Antari; Diah Miftahul Aini (JOMIS (Journal of Midwifery Science), 2025)
The global maternal mortality rate is 152 deaths per 100,000 live births. This number is about twice as high as SDG's target of 70 deaths per 100,000 live births. One of the causes of maternal death is prolonged labour caused by uterine contraction disorders and anxiety disorders of labour pain at the active first stage, resulting inadequate contractions. This Study was to analyze the effectiveness of deep breathing relaxation techniques on the labour pain level during the active first stage. The method used was pre-experimental research, with a sample size of 20 mothers giving birth. The samples were determined using total sampling techniques based on inclusion criteria. The results of this study revealed that the average pain scale at the active first stage of labour in the pre-test was (M) = 2,7 with Standard Deviation (SD) = 0,5 which showing the patient's discomfort during contractions in the first active stage of labour. After demonstrating the deep breathing relaxation technique, the average pain scale decreased to (M) = 1,6 and SD = 0,6, which indicates a successful intervention. Indicate that labour pain during the active phase has a significance of 0.000. This study concluded that deep breathing relaxation technique therapy for labour pain is effective to reduce labour pain during the active first stage